Who we are Asians - New Strategist Publications, Inc. (Amityville, New York : New Strategist Press, LLC, 2016)
Provides detailed estimates of the numbers of Asians nationally and by state and metropolitan area. Also includes the latest socioeconomic data on the Asian population. Provides detailed spending data for Asian households. Results from the American Time Use Survey are also presented, profiling Asian time use and comparing it to the averages.
chapter 1. Education -- chapter 2. Health -- chapter 3. Housing -- chapter 4. Income -- chapter 5. Labor force -- chapter 6. Living arrangements -- chapter 7. Population -- chapter 8. Spending -- chapter 9. Time use -- chapter 10. Wealth.
Includes bibliographical references and index.
Keywords: Asian Americans -- Population -- Statistics; Demographic surveys -- United States; Market surveys -- United States; Electronic books